3(b+3)+4(b+2)+b=89

Simple and best practice solution for 3(b+3)+4(b+2)+b=89 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(b+3)+4(b+2)+b=89 equation:


Simplifying
3(b + 3) + 4(b + 2) + b = 89

Reorder the terms:
3(3 + b) + 4(b + 2) + b = 89
(3 * 3 + b * 3) + 4(b + 2) + b = 89
(9 + 3b) + 4(b + 2) + b = 89

Reorder the terms:
9 + 3b + 4(2 + b) + b = 89
9 + 3b + (2 * 4 + b * 4) + b = 89
9 + 3b + (8 + 4b) + b = 89

Reorder the terms:
9 + 8 + 3b + 4b + b = 89

Combine like terms: 9 + 8 = 17
17 + 3b + 4b + b = 89

Combine like terms: 3b + 4b = 7b
17 + 7b + b = 89

Combine like terms: 7b + b = 8b
17 + 8b = 89

Solving
17 + 8b = 89

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-17' to each side of the equation.
17 + -17 + 8b = 89 + -17

Combine like terms: 17 + -17 = 0
0 + 8b = 89 + -17
8b = 89 + -17

Combine like terms: 89 + -17 = 72
8b = 72

Divide each side by '8'.
b = 9

Simplifying
b = 9

See similar equations:

| 11=-3+z | | 24x+4=19x+4 | | 3x-(4x+6)=x-9 | | 11=-4.9t^2+120t | | 10x^2+12x-1=4x | | 8-(5/7)x-32 | | 2w+3(w+2)+2(w+5)=44 | | -10+k=10-9k | | -9j+10=10j | | -4a+16+6a=-9a | | (7x+3)(x-5)=-2x(5x+6)+x-19 | | -6-7f=-6f | | X-27=84 | | t-10=10-9t | | 2+7cosx=4sin^2x | | 12x+14=134 | | y+2(y+3)+3(y+1)=45 | | 4p-7.3=16.7 | | 8-2w=-w | | -6n=-6-7n | | 8r+10=9r | | 1/5n=-8 | | 2r+3(r+3)+3r=1 | | x^2+18x+73=-9 | | y=-4.9t^2+120t | | 270=920(1-d) | | 8.7=3.5m-3.5(5.4-6m) | | 4a+5(a+3)+-14=64 | | -10-3p=10-5p-8 | | 4m^2n-6n^2-2mn= | | 3(5z+1)-12=13z+3 | | -2-6=-8u |

Equations solver categories